Effect of Physical and Chemical Hair Removal Methods on Skin Barrier Function in vitro: Consequences for a Hydrophilic Model Permeant - Pany, Astrid; Klang, Victoria; Brunner, Marion; Ruthofer, Johanna; Schwarz, Elisabeth; Valenta, Claudia (Skin pharmacology and physiology, 2019)
Background: Although very common in our society, the effect of hair removal on physiological skin parameters and on the ingress of applied chemicals has not been systematically investigated. Thus, as a first step, the aim of the present study was to elucidate the effect of hair removal through epilation (electric epilation, waxing) and depilation (dry and wet shaving, depilatory cream) on skin properties in vitro using the porcine ear model. Methods: Attenuated total reflection Fourier transform infrared spectroscopy, measurement of the transepidermal water loss (TEWL), visualization by capacitance-based contact imaging, confocal Raman spectroscopy (CRS), diffusion cell studies and tape stripping experiments were employed. Results: Increased TEWL and altered skin permittivity maps were observed. Decreased stratum corneum thickness was observed after waxing. Diffusion cell studies showed increased skin permeation especially in case of dry shaving, electric epilation and waxing. Conclusion: Considering CRS and diffusion cell data, a moderate if significant decrease in skin barrier function was found after hair removal by dry shaving (physical skin/material interaction) and epilation methods (plucking out the entire hair, for example, by electrical epilation and waxing). Subsequent experiments will include testing of different permeants covering a broad range of physicochemical properties in vitro and confirming our findings in vivo.